Elucidating The Mechanism Of Action Of Caffeic Acid Phenethyl Ester (Cape) Via Transcriptomic Profiling Of Burkholderia Pseudomallei Strain K96243 - Hasan, Norshima Abu (2019)
Burkholderia pseudomallei is a Gram-negative bacterial pathogen that causes melioidosis, a life-threatening disease endemic in the regions of Southeast Asia, particularly Malaysia and Thailand. B. pseudomallei is intrinsically resistant to wide classes of clinically useful antibiotics, such as aminoglycosides, macrolides, β-lactams, and older-generation cephalosporins. The expression of multiple efflux pumps and the low permeability of the bacterium’s outer membrane contribute to its multidrug-resistant (MDR) traits, which further complicate the therapeutic management for melioidosis. Thus, a promising strategy to minimize the resistance level of MDR bacteria is by the use of non-antibiotic helper compounds as an adjuvant to potentiate the antimicrobial activity of antibiotics. In this study, the potential of caffeic acid and its derivatives, i.e. caffeic acid phenethyl ester (CAPE), chlorogenic acid, and caffeic acid phenethyl amide (CAPA) to act as antibiotic potentiators in B. pseudomallei were evaluated. We demonstrated that the combination of a sub-inhibitory concentration of CAPE with gentamicin or kanamycin significantly reduced the MIC of these antibiotics in B. pseudomallei by four-fold and two-fold, respectively. Scanning electron microscopy further revealed that the fitness of the cells treated with CAPE were compromised, with apparent phenotypic changes to the cell morphology and disruption in the membrane architecture, such as shrunken, deformed shape and formation of membrane blebs and dimples.